2002
DOI: 10.1210/rp.57.1.129
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of the Follicle-stimulating Hormone Receptor in Spermatogenesis

Abstract: Results from experiments using mouse models suggest that the role of follicle-stimulating hormone (FSH) in spermatogenesis is the regulation of Sertoli cell proliferation and, ultimately, the size and spermatogenic capacity of the testis. The regulation of the expression of the FSH receptor (FSHR) gene is very cell specific and plays an initial role in the ultimate response of the Sertoli cells to FSH. The extreme cell specificity and the importance of the FSH response to spermatogenesis have led to an extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 78 publications
3
34
0
Order By: Relevance
“…It is well known that FSH plays a key role in the control and maintenance of normal gametogenesis through Sertoli cells (Nieschlag et al 1999, Heckert & Griswold 2002 or ovarian granulosa cells (Gromoll et al 1996, O'Shaughnessy et al 1996. Most interestingly, in this study, to accompany an increase of Af-6 expression, Usp9x was also found to be synchronously up-regulated in granulosa cells of the late-secondary and Graafian follicles in the ovaries treated with PMSG.…”
Section: Discussionsupporting
confidence: 63%
“…It is well known that FSH plays a key role in the control and maintenance of normal gametogenesis through Sertoli cells (Nieschlag et al 1999, Heckert & Griswold 2002 or ovarian granulosa cells (Gromoll et al 1996, O'Shaughnessy et al 1996. Most interestingly, in this study, to accompany an increase of Af-6 expression, Usp9x was also found to be synchronously up-regulated in granulosa cells of the late-secondary and Graafian follicles in the ovaries treated with PMSG.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, the LH receptor is expressed mainly in Leydig cells but is also mildly expressed in spermatogenic cells (22,23). The main function of FSH is to stimulate the proliferation of Sertoli cells during puberty, whereas LH regulates the synthesis of testosterone in the adult testes (24). Administration of morphine is associated with a suppression of LH release, whereas opioid antagonists such as naloxone and naltrexone produce increased serum levels of LH in humans and many animal species (25,26).…”
Section: Hormonal Control Of Reproductive Function By the Opioid Systemmentioning
confidence: 99%
“…To bypass these effects, which would preclude adjudin from being developed into a male contraceptive for human use, this drug would have to be delivered directly to the testis. To achieve this, adjudin was conjugated to a recombinant FSH mutant protein, which served as its "carrier" to the testis , because FSH receptors are restricted to Sertoli cells in the testis (Heckert and Griswold, 2002;Walker and Cheng, 2005;Hermann and Heckert, 2007) (Fig. 11).…”
Section: F Current Status Of Adjudin Researchmentioning
confidence: 99%